Words spoken true [large type] - Gabhart, Ann H., 1947- (Center Point Large Print, 2012)
"Adriane Darcy was practically raised in her father's newspaper offices. She can't imagine life without the clatter of the press and the push to be first to write the news that matters. Their Tribune is the leading paper in Louisville in 1855. Then Blake Garrett, a brash young editor from the North with a controversial new style of reporting, takes over failing competitor the Herald, and the battle for readers gets fierce. When Adriane and Blake meet at a benefit tea, their surprising mutual attraction is hard to ignore. Still, Blake is the enemy, and Adriane is engaged to the son of a powerful businessman who holds the keys to the Tribune's future. Blake will stop at almost nothing to get the story--and the girl. Can he do both before it's too late?" -- Cover verso.